Evaluating four motivation‐phase intervention components for use with primary care patients unwilling to quit smoking: a randomized factorial experiment. (19th May 2021) - Cook, Jessica W.; Baker, Timothy B.; Fiore, Michael C.; Collins, Linda M.; Piper, Megan E.; Schlam, Tanya R.; Bolt, Daniel M.; Smith, Stevens S.; Zwaga, Deejay; Jorenby, Douglas E.; Mermelstein, Robin
Abstract: Aims: To assess the effectiveness of intervention components designed to increase quit attempts and promote abstinence in patients initially unwilling to quit smoking. Design: A four‐factor, randomized factorial experiment. Setting: Sixteen primary care clinics in southern Wisconsin. Participants: A total of 577 adults who smoke (60% women, 80% White) recruited during primary care visits who were currently willing to reduce their smoking but unwilling to try to quit. Interventions Four factors contrasted intervention components administered over a 1‐year period: (i) nicotine mini‐lozenge versus none; (ii) reduction counseling versus none; (iii) behavioral activation (BA) counseling versus none; and (iv) motivational 5Rs counseling versus none. Participants could request cessation treatment at any time. Measurements: The primary outcome was 7‐day point‐prevalence abstinence at 52 weeks post enrollment; secondary outcomes were point‐prevalence abstinence at 26 weeks and making a quit attempt by weeks 26 and 52. Findings: No abstinence main effects were found but a mini‐lozenge × reduction counseling × BA interaction was found at 52 weeks; P = 0.03. Unpacking this interaction showed that the mini‐lozenge alone produced the highest abstinence rate (16.7%); combining it with reduction counseling produced an especially low abstinence rate (4.1%). Reduction counseling decreased the likelihood of making a quit attempt by 52 weeks relative to no reduction counseling ( P = 0.01). Conclusions: Nicotine mini‐lozenges may increase smoking abstinence in people initially unwilling to quit smoking, but their effectiveness declines when used with smoking reduction counseling or other behavioral interventions. Reduction counseling decreases the likelihood of making a quit attempt in people initially unwilling to quit smoking.